Blogging for dummies - Bair, Amy Lupold; Gardner, Susannah; Gardner, Susannah (Hoboken, NJ John Wiley and Sons, Inc., 2014)
The blogosphere keeps changing and evolving, and so does this top blogging guide. A terrific book whether you're just starting out or are already blogging regularly, this book provides solid information on blogging basics, the anatomy of a good blog, and the tools you need to get started. You'll learn how to set up an account, find ample coverage of social plug-ins and emerging platforms like Squarespace and Overblog, and discover savvy ways to write your first post. Best of all, the book explores how you can make real money from your passion and become a professional blogger.
Getting started with blogging. Discovering blog basics ; Entering the blogosphere ; Choosing and hosting blog software -- Setting up your blog. Starting a Blogger blog ; Starting a WordPress blog ; Starting a Tumblr blog ; Creating a Squarespace blog -- Fitting in and feeling good. Finding your niche ; Creating great content ; Building community with comments ; Blogging anonymously -- Going beyond words. Working with photos ; Starting a podcast ; Diving into vlogging ; Leveraging community with forums -- Marketing and promoting your blog. Reaching out with RSS ; Joining the Twitterverse ; Diving into social networking ; Measuring blog presence -- Getting business-y with it. Making mad mad money ; Blogging for companies -- The part of tens. Ten ways to grow community ; Ten things all bloggers should do.
Previous edition: by Susannah Gardner and Shane Birley. 2012.
Includes index.
Keywords: Blogs